Solvation Effects on the Structure and Stability of Alkali Metal Carbenoids. Issue 1 (3rd November 2020) - Dilchert, Katharina; Schmidt, Michelle; Großjohann, Angela; Feichtner, Kai‐Stephan; Mulvey, Robert E.; Gessner, Viktoria H.
Abstract: s‐Block metal carbenoids are carbene synthons and applied in a myriad of organic transformations. They exhibit a strong structure–activity relationship, but this is only poorly understood due to the challenging high reactivity and sensitivity of these reagents. Here, we report on systematic VT and DOSY NMR studies, XRD analyses as well as DFT calculations on a sulfoximinoyl‐substituted model system to explain the pronounced solvent dependency of the carbenoid stability. While the sodium and potassium chloride carbenoids showed high stabilities independent of the solvent, the lithium carbenoid was stable at room temperature in THF but decomposed at −10 °C in toluene. These divergent stabilities could be explained by the different structures formed in solution. In contrast to simple organolithium reagents, the monomeric THF‐solvate was found to be more stable than the dimer in toluene, since the latter more readily forms direct Li/Cl interactions which facilitate decomposition via α‐elimination. Abstract : Whereas in conventional organolithium chemistry unsolvated dimers are generally more stable than solvated monomers and their sodium and potassium analogues are less stable still, curiously this trend seems to be reversed in carbenoid systems. DOSY‐NMR, SC‐XRD analyses and computational studies on a chiral test system show dramatic changes in the stability depending on the solvent and the formed structures.